A coupled thermo-hydro-mechanical finite element formulation for curved beams in two-dimensions. (November 2018) - Cui, Wenjie; Potts, David M.; Zdravković, Lidija; Gawecka, Klementyna A.; Taborda, David M.G.; Tsiampousi, Aikaterini
Abstract: To enable the use of beam elements in the modelling of coupled thermo-hydro-mechanical (THM) geotechnical problems, a fully coupled and robust THM formulation is required. This paper presents such a formulation which allows both fluid flow and heat transfer along a 2D curved beam, while ensuring compatibility with coupled THM solid elements commonly used to discretise soils. Verification exercises and application with the proposed coupled beam element are carried out to demonstrate its satisfactory behaviour. The results of these analyses are compared against closed form solutions, solutions obtained using solid elements, and field measurements, showing an excellent agreement.